Shocks and their consequences across and within households in rural Zimbabwe - Hoddinott, John F. (Informa UK Limited, 2006)
Increasing attention is now being paid to poverty dynamics in developing countries. This work links the extent to which households smooth consumption or smooth assets given income shocks, the empirical evidence on the churning of households in and out of poverty, and the possibility that temporary shocks can have permanent consequences. Using longitudinal data from rural Zimbabwe, this paper extends the discussion of these issues by disaggregating the impact of shocks by levels of asset holdings, by disaggregating the impact of shocks on individual level welfare and by assessing the extent to which such shocks have permanent consequences. By doing so, it assesses the validity of distinguishing between asset and consumption smoothing and provides insights into whether poverty dynamics assessed at the household level provide an adequate picture of dynamics at the individual level.